Evaluating BIM's Impact on Project Performance in the AEC Industry of the Mena Region - MNAEDAH, MIGSID HUSAM ABDULAMEER (İstanbul Kültür Üniversitesi, 2024)
The construction industry typically faces challenges, including project delays, cost overruns, and resource shortages. These problems can be solved by managing data coordination in traditional approaches and communication between stakeholders involved in the project. However since the field of construction is characterized by complexity and a large number of activities, the implementation of these procedures becomes an obstacle for the decision-makers. The goal of this investigation is to refute this limitation and demonstrate the intended implementation of innovative information management techniques. It examines the degree to which various aspects of building information modeling (BIM) technology impact project performance domains, as well as the extent to which project performance domains are adopted and the implementation levels of BIM aspects. During this study, after examining the adoption level of performance domains and BIM aspects and performing correlation analysis to examine the relationship between them, multiple regression analysis was performed to calculate the impact of BIM aspects on project performance domains. The study conducted a survey of 153 professionals in the Middle East and North Africa (MENA) region, which revealed substantial geographical disparities in the adoption of building information modeling (BIM) and underscored the correlation between team experience, complexity, and BIM implementation levels. In addition to identifying domains where BIM integration presents challenges, ordinal logistic regression models further elucidate the positive impacts of BIM's information management and integration on performance domains such as stakeholder satisfaction and team collaboration. The integration of BIM aspects into the performance domain, the development of targeted solutions, the analysis of process paths, the identification of operational voids, and the creation of detailed models have a substantial impact on the success of projects and the optimization of decision-making processes for professionals in the fields of Architecture, Engineering, and Construction (AEC).
Yapı Bilgi Modelleme (BIM) Yaklaşımının Mena Bölgesi AEC Sektörü Proje Performansı Üzerindeki Etkisinin Değerlendirilmesi
Yüksek lisans tezi.
Keywords: Industrial and Industrial Engineering